Effect of family management styles on the outcomes of children with complex congenital heart disease after palliative surgery - Yuxian Xia; Rui Yang; Yuemeng Zhang; Di Yin; Wen Zhang; Qi Jiang; Yifan Zhu; Haibo Zhang; Renjie Hu; Wei Dong (Frontiers in Pediatrics)
BackgroundThis study aimed to explore family management style (FMS) after palliative surgery in children with complex congenital heart disease (CCHD) and evaluate its influence on their outcomes.MethodsA cross-sectional survey was conducted among 252 families of children with CCHD who underwent palliative surgery at our center. The Family Management Measure was used to investigate their FMS, and the outcomes with different FMSs were analyzed. Cluster analysis was employed to classify the FMSs into distinct groups.ResultsThe cluster analysis identified four FMSs, namely, the Active and Collaborative (Cluster 1, 29.37%), the Chaotic and Nervous (Cluster 2, 10.71%), the Confident and Caring (Cluster 3, 22.22%), and the Laissez-Faire style (Cluster 4, 37.70%). Children in Cluster 1 demonstrated the highest quality of life, while those in Cluster 2 had the lowest (73.93 ± 12.71 and 59.03 ± 18.70, P < 0.01). The unplanned readmission rates were significantly higher in Clusters 2 and 4 (18.52% and 22.11%) compared to Clusters 1 and 3 (4.05% and 3.57%, P < 0.01).ConclusionThe findings highlight the significant influence of FMS on the outcomes of children with CCHD following palliative surgery. The children in Cluster 1 exhibited the most favorable quality of life, whereas those in Cluster 2 had the worst. Health professionals should implement interventions to optimize FMS.